Cover Feature: Sulfation Patterns of Saccharides and Heavy Metal Ion Binding (Chem. Eur. J. 52/2019). Issue 52 (26th July 2019) - Alshanski, Israel; Blaszkiewicz, Joanna; Mervinetsky, Evgeniy; Rademann, Jörg; Yitzchaik, Shlomo; Hurevich, Mattan
Abstract : A sulfation‐controlled binding of heavy metal ions to glycans was realized using electrochemical analysis. The artwork presents glassy carbon electrodes modified by a series of hyaluronans with similar sizes but different sulfation patterns. The binding of heavy metal ions to these surfaces resulted in changes of the layer density that produced impedimetric response. The impedimetric response revealed that the selectivity of the hyaluronans to a specific metal ion depends on their sulfation pattern. More information can be found in the Full Paper by J. Rademann, S. Yitzchaik, M. Hurevich, et al. on page 12083 .